If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + -3x) = (5 + -4x) Remove parenthesis around (2 + -3x) 2 + -3x = (5 + -4x) Remove parenthesis around (5 + -4x) 2 + -3x = 5 + -4x Solving 2 + -3x = 5 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2 + -3x + 4x = 5 + -4x + 4x Combine like terms: -3x + 4x = 1x 2 + 1x = 5 + -4x + 4x Combine like terms: -4x + 4x = 0 2 + 1x = 5 + 0 2 + 1x = 5 Add '-2' to each side of the equation. 2 + -2 + 1x = 5 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = 5 + -2 1x = 5 + -2 Combine like terms: 5 + -2 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| -13-8a-4a=-5 | | 90x^4+21x^3-45x^2=0 | | 6y-8=11y+17 | | 7x+8=7(x-9) | | 25n^2+10n+1+25n+5-6=0 | | (2y+50)=(3y+40) | | -7(6x-8)+7=-42x+63 | | 72x^4+36x^3-260x^2=0 | | 5x+1=2(2x-4)+9 | | 3x^2-17x+2=0 | | 7x+2x=2x+7 | | x^4-12x^2+4x+24=0 | | p2-1=8/x | | .67y+6=y | | 2(x-3)2-8=0 | | -3x+8(x-5)=16x+6-8x | | -16t^2+140t+37=0 | | 1.28=(X-40/3) | | 1.28=x-40/3 | | 13=z/-2 | | 11x-15x=28 | | x^2-12x-988=0 | | t/-3=9 | | b-3/-2=-10 | | 16x-8x-12=4+20 | | X*x+3x-4=6 | | 4w-2=0 | | 2(x+2)+5x=3(2x-1) | | 2(x+2)+5x=3 | | 5n+30=y | | (5x+2)=(8x-7) | | V=l*8*12 |